2021
DOI: 10.3390/nu13103300
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiota in Korean Children with Autism Spectrum Disorders

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social and behavioral impairments. Recent studies have suggested that gut microbiota play a critical role in ASD pathogenesis. Herein, we investigated the fecal microflora of Korean ASD children to determine gut microbiota profiles associated with ASD. Specifically, fecal samples were obtained from 54 children with ASD and 38 age-matched children exhibiting typical development. Systematic bioinformatic analysis revealed that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…However, consistent results were not obtained. Five studies revealed a decreased Bacteroidetes/Firmicutes ratio in ASD [31,39,44,49,55]. Contradictory ndings were reported by the same number of authors [34,36,38,47,48], and in three other studies, no signi cant changes were observed [29,35,37].…”
Section: Gut Bacteria Pro Les In Children With Autism Spectrum Disordermentioning
confidence: 79%
See 4 more Smart Citations
“…However, consistent results were not obtained. Five studies revealed a decreased Bacteroidetes/Firmicutes ratio in ASD [31,39,44,49,55]. Contradictory ndings were reported by the same number of authors [34,36,38,47,48], and in three other studies, no signi cant changes were observed [29,35,37].…”
Section: Gut Bacteria Pro Les In Children With Autism Spectrum Disordermentioning
confidence: 79%
“…Lower total SCFAs in stool samples of children with autism were reported in two studies [40,53], while higher levels were reported in another one [49]. Further, lower fecal acetate and butyrate [28,53] and lower propionate in autistic patients were described [53].…”
Section: Gut Bacteria Pro Les In Children With Autism Spectrum Disordermentioning
confidence: 98%
See 3 more Smart Citations